Prophecy in context: empirical and conceptual Issues of diakonia in the public space - Moos, Thorsten (Diaconia, 2020)
Take care for those who need help but don’t get too involved with politics. Surveys show this kind of common-sense attitude toward the societal role of churches and diaconical institutions is preferred in Germany. Nonetheless, German diakonia regularly goes public - in statements and comments on topical political and ethical issues. But which public role should diakonia take? And how does this role relate to current concepts of “prophetic diakonia” or “public theology”?This paper analyses diaconical contributions to some recent ethical debates within the framework of public religious institutions. It thus contributes to a theory of public religion which considers the differences between various social forms and institutional contexts of religion. This should be helpful to better understanding what “prophecy” might mean in the context of modern societies within a globalized world.
Gesehen am 26.11.2021